2011
DOI: 10.1371/journal.pone.0018817
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-Dependent Control of Class II MHC Localization Is Dispensable for Antigen Presentation and Antibody Production

Abstract: Controlled localization of class II MHC molecules is essential for proper class II MHC-restricted antigen presentation and the subsequent initiation of an adaptive immune response. Ubiquitination of class II MHC molecules on cytosolic lysine (K225) of the β-chain has been shown to affect localization of the complex. We generated mice in which the endogenous β-chain locus is replaced with a GFP tagged mutant version that lacks the cytosolic lysine residue (I-A-β-K225R-EGFP). These mice have elevated levels of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
1
14
1
Order By: Relevance
“…Knock-in mice for a ubiquitination mutant of MHCII showed dysfunction of DCs similar to that of MARCH1 knockout mice ). Others concluded that ubiquitin-dependent control of MHCII localization is dispensable for antigen presentation and antibody production (McGehee et al 2011). In the latter study, mice in which endogenous MHCII was replaced by GFP-tagged wildtype MHCII were compared with knock-in mice for a K225 ubiquitination mutant of GFP-tagged MHCII.…”
Section: Sorting Of Mhcii At Mvbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Knock-in mice for a ubiquitination mutant of MHCII showed dysfunction of DCs similar to that of MARCH1 knockout mice ). Others concluded that ubiquitin-dependent control of MHCII localization is dispensable for antigen presentation and antibody production (McGehee et al 2011). In the latter study, mice in which endogenous MHCII was replaced by GFP-tagged wildtype MHCII were compared with knock-in mice for a K225 ubiquitination mutant of GFP-tagged MHCII.…”
Section: Sorting Of Mhcii At Mvbsmentioning
confidence: 99%
“…MHCII peptide loading and ubiquitinaton are not necessarily mechanistically linked, and the sequence of events could merely be dictated by differences in kinetics. A second indication for MHCII peptide loading at the endosomal-delimiting membrane is that loading of wild-type MHCII and mutant K225 MHCII were equally efficient (Shin et al 2006;van Niel et al 2006), and that antigen presentation was unaffected in ubiquitination-deficient MHCII knock-in mice (McGehee et al 2011). Third, interference with MHCII sorting at MVBs with a dominant-negative mutant of VPS4 also did not affect peptide loading (T ten Broeke, R Wubbolts, W Stoorvogel, et al, unpubl.).…”
Section: Mvb Dynamics and Mhcii Peptide Loadingmentioning
confidence: 99%
“…In immature dendritic cells MHC II beta chain engineered to not accept ubiquitin (by mutating single lysine in the cytoplasmic tail for arginine) remained at the plasma membrane, while a ubiquitin fused directly to the MHC II beta chain showed decreased surface expression (Ma et al, 2012). Again, McGehee et al (2011) reported a mouse with engineered MHC II molecules unable to accept uniquitin and could not observed any effect on MHC II distribution and other processes dependent of MHC II such as antibody production. Various experiments reported effects of ubiquitin modifications on endosomal behavior of various proteins, including MHC II.…”
Section: Current Statusmentioning
confidence: 99%
“…What directs trafficking of MHC II through the early endosome? Recent evidence suggests that a lysine residue of the MHC class II b-chain (K 225 of mouse I-A b ) and its monoubiquitination by the MARCH-I E3 ubiquitin ligase regulate the trafficking of MHC class II in both mice and humans [59][60][61][62][63][64] but the issue is clearly complicated. MHC class II ubiquitination by MARCH-I results in a low level of surface MHC class II and this tightly regulated process is blocked by DC maturation [65].…”
Section: The ''Recycling'' Pathwaymentioning
confidence: 99%
“…Despite this, a firm link between MHC ubiquitination and T CD4? responses has yet to be established [61,62,65]. Exploration of these issues in well-defined antigen systems may provide traction.…”
Section: The ''Recycling'' Pathwaymentioning
confidence: 99%